2019
DOI: 10.2139/ssrn.3476536
|View full text |Cite
|
Sign up to set email alerts
|

Do Expert Panelists Herd? Evidence from FDA Committees

Abstract: We develop a structural model to address the question whether, and to what extent, expert panelists engage in herd behavior when voting on important policy questions. Our data comes from FDA advisory committees voting on questions concerning the approval of new drug applications. We utilize a change in the voting procedure from sequential to simultaneous voting to identify herding. Estimates suggest that around half of the panelists are willing to vote against their private assessment if votes from previous ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Further to the drug testing phase, another study looked into FDA advisory and expert committees which deliberate and vote on yes-or-no questions about new drug applications. Newham 6 found that sequential voting tends to sway or "herd" half of the members who take vote history (i.e. preceding votes) into consideration.…”
Section: Drug Development: Choices Biases and Conflicts Of Interestmentioning
confidence: 99%
“…Further to the drug testing phase, another study looked into FDA advisory and expert committees which deliberate and vote on yes-or-no questions about new drug applications. Newham 6 found that sequential voting tends to sway or "herd" half of the members who take vote history (i.e. preceding votes) into consideration.…”
Section: Drug Development: Choices Biases and Conflicts Of Interestmentioning
confidence: 99%